Role of Women Fish Workers for Food Security in Assam - Deepjyoti Baruah (Journal of Krishi Vigyan, 2015)
Women fish workers in Assam play a critical role within the aquaculture and fishing communities, roles that are often not recogniz ed or supported. Women are particular ly active in fish culture, fish capturing by traditional and indigenous methods and in postharvest fisheries by engaging themselves as fish vendors. These women have to face several socio-cultural taboos who strive to earn for their family’s subsistence in rural areas. To ensure the utilization of their full potential in profitable activities like aqua farming, it is necessary to provide capacity building support to rural women, which will eventually lead to their empowerment and food security to their household. This paper discusses on the occupational status of women fish workers in the state and the promising aspects in aquaculture and fisheries which can provide immense scope for improving the livelihood of rural women